Efektivitas Bimbingan Kelompok dengan Teknik Reframing untuk Mengatasi Rendahnya Kepercayaan Diri Siswa Berbicara di Depan Umum - Siti Hartina; Syarifudin Syarifudin; Yasintha Sari Pratiwi; Muhaimin Abdillah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the effectiveness of group guidance with reframing techniques in overcoming students' low confidence in public speaking. The study was conducted at SMK Negeri 7 Samarinda, Samarinda City. This study used a quantitative approach with a quasi-experimental method with a non-equivalent control group design. The research subjects were 16 students divided into an experimental group and a control group of 8 students each. The data collection technique used a public speaking confidence scale in the form of a Likert scale. The instrument has been tested for validity with the Pearson correlation technique and tested for reliability using Alpha Cronbach. In addition to the scale, data were also obtained through observation and interviews to describe the conditions and behavior of students during the service process and after the treatment process was carried out. Data analysis techniques in this study included prerequisite analysis and hypothesis testing. Prerequisite analysis was carried out with a normality test using Shapiro-Wilk and a homogeneity test using the Levene test through the SPSS version 25 program. Furthermore, hypothesis testing was carried out using an independent samples t-test. Score improvement analysis was also carried out using N-gain to measure changes in pre-test and post-test scores in each group. The results showed a significant difference between the experimental and control groups after treatment, with a 2-tailed significance value of 0.028 (p < 0.05). The experimental group's posttest average was 88.2, higher than the control group's 76.3. The experimental group's average N-gain score was 0.6945, higher than the control group's 0.3296. These findings indicate that group guidance with the reframing technique is significantly effective, based on the difference in posttest scores and N-gain scores, in increasing students' confidence in public speaking and can be an alternative service for guidance and counseling teachers in schools.